Kebutuhan Dimensi Sumur Resapan untuk Pemukiman Padat di Kelurahan Mandalika Kota Mataram - Saidah, Humairo; Sulistiyono, Heri; Wiradarma, Lalu Wirahman (LPPM Universitas Mataram, 2025)
The rapid development of residential areas in Mataram City has led to significant changes in land use, potentially increasing surface runoff and causing issues such as surface ponding and localized flooding. One feasible solution to mitigate these impacts is the construction of infiltration wells as a form of sustainable and environmentally friendly drainage infrastructure. This study aims to provide technical guidance to the community in one of the densely populated sub-districts of Mataram City for determining the appropriate dimensions of rainwater infiltration wells based on field data. The design rainfall was estimated through frequency analysis using a normal distribution. Rainfall intensity was calculated using the Mononobe method, and runoff discharge was analyzed using the Rational method. Infiltration wells were then designed using the Sunjoto method and applied to residential units in the Mandalika Subdistrict, with variations in building area and land area (LB/LT) ranging from 24/60 to 60/70 square meters. Based on soil testing, the study area has an average soil permeability coefficient of 3.16 cm/hour and an average groundwater table depth of 2.45 meters. The results of the analysis for various house types from small to large, if the well is circular Ø 1.0 meters, then each house needs 1 well with a depth of between 1.14 meters to 1.97 meters, while for a well Ø 0.8 meters, it requires 1 well with a depth (H) between 1.76m to 3.03m. Especially for houses with a roof area of more than 60m2, a well with Ø 0.8 meters requires a depth exceeding the local groundwater level so it is recommended to make 2 or can also use Ø 1.0 meters. The dimensions of the well have been in accordance with the capacity requirements based on rainfall and the position of the local groundwater level.